IMPLEMENTASI NILAI-NILAI KELAHIRAN PANCASILA DALAM MEMBENTUK KARAKTER MORAL MAHASISWA DI LINGKUNGAN KAMPUS. - Akdila Bulanov; Muhammad Lukman; Vecilla Qirania Khaira; Wihariyati; Nesha Karmilia Putri; Refo Bilal Pramuza (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The moral degradation of students in the era of globalization is a real challenge for the world of higher education, thus requiring the revitalization of moral instruments. This study aims to examine and analyze the implementation of the values of the birth of Pancasila in shaping the moral character of students in the university environment. The research method used is a literature review or library study by analyzing five relevant national journals obtained from trusted scientific databases. The data collection technique was carried out by identifying, selecting, and reviewing the contents of the journals, which were then analyzed using a qualitative descriptive approach through a process of synthesizing literature findings. The results of the analysis show that the reconstruction of the historical essence of the birth of Pancasila has a significant positive correlation with the strengthening of student morality. The formation of religious, ethical, honest, and responsible character can be realized through three integrative strategies on campus, namely: strengthening the Pancasila Education curriculum material as an ethical system, providing real examples (role models) from lecturers, and implementing a consistent campus disciplinary culture. In conclusion, the values of the birth of Pancasila play a central role as the foundation and main moral foundation in higher education. The synergy of all academic elements in implementing Pancasila values has proven effective in producing a young generation with integrity and nationalism, so that students are able to carry out their function as agents of change.